2010
DOI: 10.3390/d2040527
|View full text |Cite
|
Sign up to set email alerts
|

The Rhizosphere of Coffea Arabica in Its Native Highland Forests of Ethiopia Provides a Niche for a Distinguished Diversity of Trichoderma

Abstract: The southwestern highlands forests of Ethiopia are the origin of the coffee plant Coffea arabica. The production of coffee in this area is affected by tracheomycosis caused by a soil-born fungus Gibberella xylarioides. The use of endemic antagonistic strains of mycoparasitic Trichoderma species would be a nature conserving means to combat this disease. We have used molecular methods to reveal that the community of Trichoderma in the rhizosphere of C. arabica in its native forests is highly diverse and includes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…This could explain, at least partially, the abundance of Trichoderma species in rhizosphere of coffee plants. 17 Caffeine-producing plants directly benefit from Trichoderma species to cope with pathogens. In addition, host plants also indirectly benefit from Trichoderma species through activation of plant growth potential, priming for defense reaction and antibiotic production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could explain, at least partially, the abundance of Trichoderma species in rhizosphere of coffee plants. 17 Caffeine-producing plants directly benefit from Trichoderma species to cope with pathogens. In addition, host plants also indirectly benefit from Trichoderma species through activation of plant growth potential, priming for defense reaction and antibiotic production.…”
Section: Discussionmentioning
confidence: 99%
“…16 The idea was partially substantiated by a finding that rhizosphere of Coffea arabica in Ethiopian highlands was rich in species of filamentous fungus, Trichoderma. 17 Diverse Trichoderma species were also found among coffee endophytic fungi that colonize healthy tissues. 18,19 Trichoderma population was enriched in coffee waste containing caffeine »0.1% in wet weight.…”
Section: Introductionmentioning
confidence: 99%
“…Donc, le milieu naturel à base de pomme de terre (PDA) se révèle être le milieu le plus adéquat pour la culture de Trichoderma vus les composés complexes qui le constituent par rapport aux milieux synthétiques (MEA, SB, DOX) qui sont moins favorables à la croissance des souches. Ces résultats sont en accord avec ceux obtenus par Ubalua et OtiE (2007), Verma (2007, Moussaoui (2010), Jahan et al (2013), Srivastava et al (2014) (Kubicek et al, 2003 ;Zhang et al, 2005 ;Mulaw et al, 2010 ;Skoneczny et al, 2015).…”
Section: Effet De La Salinitéunclassified
“…So far, approximately 40 soil-inhabiting Trichoderma species have been recorded around the world in many publications (e.g. Kubicek et al 2003;Wuczkowski et al 2003;Yu et al 2007;Hoyos-Carvajal et al 2009;Migheli et al 2009;Mulaw et al 2010;Kredics et al 2012;Sun et al 2012;Li et al 2013;L opezQuintero et al 2013;Al-Sadi et al 2015), which accounts for a small fraction of the more than 260 known species of the genus (Chaverri and Samuels 2003;Zhu and Zhuang 2014b;Bissett et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Among the 482 isolations in soil from the Island of Sardinia, Migheli et al (2009) identified 14 species. Mulaw et al (2010) reported eight species from the 134 strains in rhizosphere soils of Coffea arabica in Native Highland Forests of Ethiopia. Kredics et al (2012) discovered 11 species among the 116 strains from chopped roots of winter wheat of five agricultural fields in the Great Hungarian Plain.…”
Section: Introductionmentioning
confidence: 98%